Motnje občutljivosti, zaznavnih in spoznavnih sposobnosti in izid rehabilitacije po možganski kapi - Goljar, Nika (Rehabilitacija (Ljubljana), 2012)
Background: The presence of sensory, cognitive and perceptual deficits often increases the severity of functional disabilities, causes emotional distress, interferes with the patient's ability to participate in and learn during rehabilitation, and increases the risk of injury. The aim of our study was to assess the prevalence of sensory, perceptual and cognitive deficits of stroke patients admitted to comprehensive rehabilitation programs and their impact on rehabilitation outcomes. Methods: Retrospective study of frequency of sensory, perceptual and cognitive deficits registered in medical documentationand of rehabilitation outcomes of stroke patients admitted to the stroke rehabilitation unit of the University Rehabilitation Institute in Ljubljana from January 1st to June 30th, 2011. Results: Eighty per cent of stroke patients had sensory deficits, and 65 percent had cognitive and perceptual deficits; 20 percent of the latter had severe communication problems. The rehabilitation outcomes of patients with cognitive and perceptual deficits were worse than those of patients without deficits, though they still showed statistically significant improvement of functioning. Conclusion: The assessment and documentation of sensory, cognitive and perceptual functions is not sufficiently systematic. We need to supplement screening measures to evaluate cognitive and perceptual functions. To improve our therapeutic approaches of cognitive and perceptual deficits we need to reform our stroke rehabilitation programs emphasizing occupational, speech and language and psychological therapies.
Keywords: cognitive deficits; izid zdravljenja; motnje somatosenzoričnih funkcij; motnje zaznavnih in spoznavnih funkcij; možganska kap; perceptual deficits; rehabilitacija; somatosensory deficits; Stroke; Treatment Outcome; vocational rehabilitation